Implementasi Pembelajaran Kitab Berbahasa Melayu Jawi pada Prathomsuksa Di Patani Thailand - Mayuso, Hakimah; Chemo, Supiyan; Lehnuh, Muhammaridwan; Madami, Usman; Nugroho, Taufik (Universitas Cokroaminoto Yogyakarta, 2024)
Traditional Islamic religious education in Patani studies the yellow book in Javanese Malay without using the government system by holding recitations in mosques or in Islamic halls. Over time, the use of Jawi Malay has decreased. One Prathomsuksah in Panyasa Panare has tried to keep going in his education. Using qualitative ethnography, research is carried out to find out how the learning process works. Parental impressions were also investigated. The learning process with the Malay Jiwa book runs every day and includes several Islamic religious lessons. The learning is also practiced by visiting the homes of parents or students who are having difficulty holding yasinan. This has given parents a good response.